Assessing Heterogeneity in Students’ Visual Judgment: Model-Based Partitioning of Image Rankings - Tallon, Miles; Greenlee, Mark W.; Wagner, Ernst; Rakoczy, Katrin; Wiedermann, Wolfgang; Frick, Ulrich (Frontiers in Psychology, 2022)
Differences in the ability of students to judge images can be assessed by analyzing the individual preference order (ranking) of images. To gain insights into potential heterogeneity in judgement of visual abstraction among students, we combine Bradley–Terry preference modeling and model-based recursive partitioning. In an experiment a sample of 1,020 high-school students ranked five sets of images, three of which with respect to their level of visual abstraction. Additionally, 24 art experts and 25 novices were given the same task, while their eye movements were recorded. Results show that time spent on the task, the students’ age, and self-reported interest in visual puzzles had significant influence on rankings. Fixation time of experts and novices revealed that both groups paid more attention to ambiguous images. The presented approach makes the underlying latent scale of visual judgments quantifiable.